Batak dan Bukan Batak: Paradigma Sosiohistoris tentang Konstruksi Identitas Etnik di Kota Medan, 1906-1939 - Hidayat Hidayat; Erond L. Damanik (Jurnal Sejarah Citra Lekha, 2018)
This research discusses the sociohistorical paradigm of Batak label construction on Mandailing and Angkola ethnicities in the city of Medan, 1906-1939. Throughout the year, the two ethnic migrants from southern Tapanuli clashed in Medan because of the Batak labeling. The Mandailing ethnic group rejected the Batak label, while the Angkola ethnic group affirmed on that label. The disputes have an impact on the division of political, economic, religious and cultural identities. The rejection from Mandailing ethnic on Batak labeling continues to occur until 2017. This research aims to describe the construction of the Batak label by answering general questions on how do the two ethnic groups fight because of the Batak label? Specifically, this article also answers the origin of Batak labeling? Why is the label debated? To explain this case, the theory of social construction is used with the sociohistorical paradigm and the case study research method. The results of the study that the Batak label is considered as a foreign ethnographic construction with a pejorative tone and disputes occur because of the strategic stability of identity as a social radar to understand the social world.